2021
DOI: 10.3390/genes12101558
|View full text |Cite
|
Sign up to set email alerts
|

Improved SNV Discovery in Barcode-Stratified scRNA-seq Alignments

Abstract: Currently, the detection of single nucleotide variants (SNVs) from 10 x Genomics single-cell RNA sequencing data (scRNA-seq) is typically performed on the pooled sequencing reads across all cells in a sample. Here, we assess the gaining of information regarding SNV assessments from individual cell scRNA-seq data, wherein the alignments are split by cellular barcode prior to the variant call. We also reanalyze publicly available data on the MCF7 cell line during anticancer treatment. We assessed SNV calls by th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Each of these components can be adapted to other applications. Recent studies emerged to infer subclone evolution from single-cell RNA sequencing (scRNA-seq) data due to its high input amount [ 46 , 47 , 48 , 49 ]. The sparsity and noise are general for single-cell data (e.g., scRNA-seq and single-cell chromatin accessibility data) and, thus, our extended RDA can be also applied to other areas of single-cell data analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Each of these components can be adapted to other applications. Recent studies emerged to infer subclone evolution from single-cell RNA sequencing (scRNA-seq) data due to its high input amount [ 46 , 47 , 48 , 49 ]. The sparsity and noise are general for single-cell data (e.g., scRNA-seq and single-cell chromatin accessibility data) and, thus, our extended RDA can be also applied to other areas of single-cell data analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that CNVs are associated with complex diseases such as autism, schizophrenia, Alzheimer’s disease, and cancer. In recent years, there have been a large number of studies on SNVs and CNVs ( Jugas et al, 2021 ; Prashant et al, 2021 ; Ladeira et al, 2022 ; Lee et al, 2022 ; Li et al, 2022 ; Zheng, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…However, new research has demonstrated that primate adrenal tissue does not originate from an adrenogenital ridge 165 . Testing whether centripetal migration is the correct model for human adrenal gland development is difficult but becoming feasible through the application of single-cell analyses, which use somatic DNA variants as barcodes for cell ancestry 167 , 168 . Questions about cell ontogeny in human adrenal are raised by the finding of juxta-medullary ZG cells, by the presence of adrenomedullary cells in the ZG 169 , 170 and by our finding that RSPO3-LGR5 signalling inhibits aldosterone production in the human adrenal gland 105 , 169 , 170 .…”
Section: Cacna1dmentioning
confidence: 99%